Analisis Pengelolaan BLUD pada BPSDMD Provinsi SUMSEL - Balqizia Shafa Shabira; Sari, Kartika Rachma; Indriasari, Desi (Economic Reviews Journal, 2024)
The implementation of the BLUD Financial Management Pattern (PPK) in the process of formation and implementation still faces a number of obstacles that result in the smooth operation of its operations are not optimal. This obstacle occurs both from the internal and external sides of BLUD. The convenience provided in the BLUD system is due to special demands, namely to improve the quality of service from BLUD. Therefore, the prerequisites for the regional apparatus to implement the Financial Management Pattern of the Regional Public Service Agency (PPK BLUD) must be carried out selectively and objectively. This study uses a descriptive analysis method with a qualitative approach. An approach to research that aims to describe or explain the observed phenomena in detail and depth. The results of this study concluded that Planning and Budgeting, administration and financial reporting of BPSDMD South Sumatra Province have been carried out in accordance with the guidelines for BLUD financial management as stipulated in Permendagri 79 of 2018 concerning BLUD but the budgeting system tends to use the Traditional Budgeting system, not purely combined with the Performance Budgeting System and financial reports have not been published directly or through existing websites so it is recommended to immediately implement the Performance Budgeting System and publish financial reports through the existing website.